Development of electrochemical chiral biosensor utilising reduced graphene oxide/collagen-modified glassy carbon electrode for enantio-recognition of chiral molecules - Kasinathan, Bavani (2016)
Enantio-recognition in chiral molecules has been attracting considerable attention due to the high selectivity of chiral molecules species in nature. The aim of this study is to fabricate and characterise the biocompatible composite material suitable for enantiorecognition. The unique structure of graphene’s honeycomb lattice leads to numerous properties, such as high thermal conductivity, good biocompatible and high specific surface area, which made graphene a promising material endlessly including in the biological field. However, the interactions with significant biomolecules have not been studied in detail. Collagen (Col), the most abundant chiral, extracellular protein was chosen as a potential chiral biomolecule to fabricate a biocompatible composite material with graphene where profoundly capable of enhancing the chiral recognition properties of the chiral molecules. Pertaining to the promising potential of this composite, preliminary electro-analysis studies have been carried out on two types of graphene conditions consisting of Reduced Graphene Oxide (RGO) and Graphene Oxide (GO) which has been incorporated into Col biopolymer correspondingly. Cyclic Voltammetry (CV) studies have been carried out in various parameters such as effect of concentrations, temperatures, pH, scan rates and multiple cycles to study the performance of the modified electrodes. The properties, structures and morphology of the composites have been studied by microscopic and spectroscopic method involving Field emission scanning electron microscopy, Transmission electron microscopy, Fourier transform infrared spectroscopy, Raman spectroscopy and Electrochemical impedance spectroscopy. The chosen composite matrix was then applied in simple chiral recognition of Mandelic Acid (MA) and Tyrosine (Tyr) enantiomers using CV and Differential pulse voltammetry (DPV), respectively. At the chosen condition, CV of L-MA and D-MA were detected at peak potential of (Ep) 1.54 V and 1.41 V, respectively, with almost similar current response of 165–190 μA using GO/Col-modified electrode. However, a good separation between the enantiomers was detected at Ep 1.51 V and 1.44 V separately with opposing current response of 235 μA and 130 μA, respectively using RGO/Col-modified electrode. Besides, the DPV measurements of L-Tyr and D-Tyr were detected at Ep 0.67 V and 0.68 V, respectively, with similar current response of 1.68–2.48 μA. Conversely, the enantiomers were detected at separate potentials of 0.66 V and 0.68 V with current responses of 3.99 μA and 2.78 μA, indicating that the RGO/Col-modified glassy carbon electrode (GCE) exhibited a better performance compared to GO/Col-modified GCE and displayed the potential in being used as good candidate for enantiorecognition of chiral molecules. Hence, RGO/Col-modified electrode was chosen to be further studied in the enantiorecognition of Salbutomol (Sal) and Epinephrine (Epine) enantiomers, respectively. Chiral recognition of Sal and Epine enantiomers were successfully accomplished by applying neither chiral selector nor mediator. The voltammetry responses of Sal enantiomers oxidation and Epine enantiomers reduction occurred on the chiral surface of RGO/Col-modified GCE were due to the high sensitivity as well as discriminating recognition ability of the modified electrode which is the crucial element in chiral recognition. The notable differences in peak current between D- and L- Sal was observed at 10.0 μmol L−1 whereas peak current between D- and L- Epine were observed at 7.5 μmol L−1 with a separation value of 414.7 nA (2.4 folds) and 1614.72 nA (1.5 folds) individually. The incorporation of RGO into Col molecules not only provides higher surface area and electrical conductivity, but also facilitated RGO becomes more hydrophilic. Besides, Col also regulates the RGO from accumulation and the assembling of RGO/Col-modified GCE has more available active sites compared to bare GCE, thus enhanced the catalytic activity. Additionally, the chiral Col molecules might also have a different binding affinity towards each of Sal and Epine enantiomers, resulting alterations in the oxidation potential in electrochemical measurements. Moreover, the electrostatic interaction between RGO and Col has been significantly projected the alteration in chiral discrimination of the enantiomers. A good reproducibility and repeatability as well as acceptable stability of chiral recognition of Sal and Epine enantiomers by RGO/Col- modified GCE offer a rapid enantio-recognition in various chiral-related industries such as pharmaceuticals and agrochemicals.